Collective Self-Reliance: Concept and reality - Volker Matthies (Intereconomics, 1979)
The concept of Collective Self-Reliance (CSR) has been of increasing political importance since the early seventies in the North-South negotiations and also at the South-South conferences (of non-aligned and Group of 77 countries), especially in connection with the discussions on a New International Economic Order (NIEO). Development researchers in poor and rich countries have at the same time begun to pay more attention to the concept of Self-Reliance (SR) in both its individual and its collective dimension. The concept of Collective Self-Reliance is examined in the following article as are its chances of realization.
Keywords: 330; Development Strategy